2013
DOI: 10.1002/ca.22242
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the coccygeal plexus

Abstract: The coccygeal plexus is variably described in anatomy texts and has rarely been studied despite the idiopathic nature of coccydynia in up to one-third of affected patients. The plexus was therefore investigated using a combination of microdissection and histology. The distal sacrum and coccyx in continuity with ischiococcygeus were removed en bloc from 16 embalmed cadavers (mean age 78 ± 10 years, 7 females) with no local disease. Ten specimens underwent microdissection of the coccygeal plexus and the remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is associated with the fifth sacral and coccygeal nerve roots and the terminal sympathetic plexus. Coccydynia is defined as pain in the coccyx and/or coccygeal joints [1-5]; it is five times more common in women than in men [6]. Pain related to coccydynia is aggravated by sitting or prolonged sitting in the same position and cycling [1, 3, 7].…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with the fifth sacral and coccygeal nerve roots and the terminal sympathetic plexus. Coccydynia is defined as pain in the coccyx and/or coccygeal joints [1-5]; it is five times more common in women than in men [6]. Pain related to coccydynia is aggravated by sitting or prolonged sitting in the same position and cycling [1, 3, 7].…”
Section: Introductionmentioning
confidence: 99%
“…It was originally described by Ricardo Plancarte in 1990 for the treatment of perianal cancer pain of visceral origin 6. Woon and colleagues reviewed the innervation of the coccygeal area and performed their own dissection which showed that the innervation of the coccyx is composed mostly of the coccygeal nerves and the lower sacral spinal nerves, which originate from the lower sacral nerve roots 7 10. The coccygeal plexus primarily innervates the anterior part of the coccyx.…”
Section: Discussionmentioning
confidence: 99%
“…It originates from the ventral rami of the sacral nerves S4 and S5 and the coccygeal nerves (figure 1). 11 The coccygeal plexus supplies the sacrospinous and coccygeal ligaments, soft tissue and skin overlying the ventral coccyx, external anal sphincter, coccygeal periosteum, sacrococcygeal joint, and anterior musculature including the ischiococcygeus, pubococcygeus, coccygeus and part of the levator ani 7 10 11. Despite a large number of coccygeal nerves are present in human embryos (up to a total of five), all but the first pair regress during embryo development 12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anococcygeal nerves originate from this plexus and function to supply the skin adjacent to the sacrotuberous ligament on the dorsal aspect of the coccyx (16,17). The coccygeal plexus has been theorized to play a role in generating the pain seen in coccygodynia, therefore making it an ideal site for neuromodulation (18).…”
Section: Discussionmentioning
confidence: 99%